EDUKASI CEK "KLIK” UNTUK MEMASTIKAN KEAMANAN JAMU DAN PRODUK PANGAN KEPADA ANGGOTA PKK KELURAHAN TANJUNG KABUPATEN BANYUMAS - Retno Wahyuningrum; Dwi Hartanti; Shintia Lintang Charisma (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The abundance of herbal medicine and food products available on the market, along with easy access to obtain them, requires vigilance regarding the safety of products consumed by consumers. Ensuring the safety of herbal medicine and food products is essential, given the discovery of several illegal cases, such as the addition of pharmaceutical chemicals, products without distribution permits, and violations of efficacy claims. The addition of in herbal medicine or food products poses serious health risks to consumers. Therefore, consumers must be cautious in selecting products before use. Considering the importance of choosing safe herbal medicine and food products, all relevant parties must focus on educating the public about how to select and ensure the safety of such products. The method used in this program is counseling about "KLIK" check (Packaging, Label, Distribution Permit, and Expiry Date) by providing leaflets, starting with a pre-test and ending with a post-test to assess participants' understanding of the educational material. Educational materials were delivered through leaflets, team presentations, and examples of herbal medicine and food products. The aim of this program is to increase knowledge and understanding of vigilance in selecting and ensuring the safety of products to prevent undesirable consequences from the use of illegal herbal medicine and food products. Analysis of the pre-test and post-test results showed an improvement in participants' knowledge and understanding. It can be concluded that this program enhanced public knowledge, particularly among members of the PKK, regarding caution and precision in choosing good and safe herbal medicine and food products.